Penentuan Nilai Peak Particle Velocity Peledakan Berdasarkan Analisis Regresi Non Linear dan US Bureau Of Mines Oriard’s Formula pada Pit Pinang PT Bukit Baiduri Energi - Djuwita Dela Safitri; Tommy Trides; Agus Winarno; Albertus Juvensius Pontus; Lucia Litha Respati (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research investigates the Peak Particle Velocity (PPV) resulting from blasting operations at Pit Pinang, PT Bukit Baiduri Energi, employing two prediction approaches: Non-Linear Geometric Regression and the USBM Oriard’s Formula. Ground vibration measurements were recorded over a one-month period, from October 9 to November 8, 2025. The findings indicate that the non-linear regression model achieves a higher predictive accuracy of 78.62%, outperforming the USBM Oriard’s Formula, which reaches 68.2%. Variations between the observed and estimated PPV values were affected by factors such as the location of geophones, differences in explosive charges, and alterations in borehole depths. In addition, the study evaluates optimal explosive charge recommendations in accordance with SNI 7571:2010 standards to mitigate potential structural damage in surrounding areas. By highlighting these predictive discrepancies and providing practical guidance on charge management, the research offers valuable insights for improving blasting safety and minimizing vibration impacts on nearby infrastructure. The comparison of methods emphasizes the importance of selecting appropriate prediction models to ensure both operational efficiency and environmental safety.